Alopecia areata treated with dimethyl fumarate: A case series. Issue 6 (4th September 2020) - Muscianese, Marta; Magri, Francesca; Leoncini, Pier Paolo; Fortuna, Maria C.; Caro, Gemma; Rossi, Alfredo
Abstract: Alopecia areata is an autoimmune condition leading to non‐scarring hair loss. Clinically, several presentations ranging from single or few small patches to complete hair loss are documented. The management of alopecia areata is challenging and all available treatments do not ensure a long‐term remission to assess the safety and efficacy of systemic dimethyl fumarate in alopecia areata patients not responding to other systemic treatments. After obtaining informed consent, we administered off‐label dimethyl fumarate to 10 adult patients with alopecia areata, for a period ranging from 4 to 37 weeks. Medical information for each patient and the severity of alopecia tool (SALT) score before and after dimethyl fumarate administration were recorded. During the treatment, 50% of patients (5 patients out of 10) had a slight improvement of hair regrowth; it was mainly as partial hair regrowth (ranging from 8% to 32%) and only one patient (10%) achieved > 50% terminal hair regrowth. Authors conclude that dimethyl fumarate is not advisable as a treatment of alopecia areata, also considering the risk of fumaric acid esters toxicity.